KONSTRUKSI INTERPOLATOR MORFOLOGI BINER 2D DENGAN METRIK HAUSDORFI - PANGGALO, MILSON
In Mathematical Morphology sense, the interpolation of binary image is considered as the problem of interpolation of sets. Let X and Y are sets representing two dierent 2D binary images, then the interpolation of these binary images will pro- duce a sequence of new images which is the transformation of the rst image (X) into another (Y ). The proposed method is based on the use of Hausdor metric h(X; Y ) = max